Organizational Complexity and Financial Reporting Quality - Tumpal Manik; Henry Eryanto (Prodi Akuntansi FEBM Universitas Maritim Raja Ali Haji, 2025)
This study examines the relationship between organizational complexity in the context of management and the quality of financial reporting. Organizational complexity is analyzed through four key components: subsidiary management, segment operation management, and human resource management. The findings provide evidence that managing organizational complexity through effective governance and sound management practices supports greater accuracy, transparency, and reliability in financial reporting. Such management practices also help prevent reporting errors and fraud. Consequently, organizational complexity can significantly influence the quality of financial reporting. Drawing on insights from agency theory and information asymmetry, this paper discusses how increasing complexity may reduce reporting quality and proposes mechanisms to mitigate its adverse effects